PENINGKATAN PRESTASI BELAJAR FISIKA MELALUI METODE EKSPERIMEN SISWA KELAS XI MIA 1 SMAN 3 BENGKALIS - SURYANI SURYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
Classroom action research on using experiment methods to inprove students physics learning achievement. Experimental learning method is a way of teaching and learning that involves students experiencing and proving themselves into process of the experimental results. With experiments, it is hoped that students can really understand the physics concepts being studied. The problem to be solved is the low achievement in learning physics as shown by the physics learning outcomes of class XI MIA 1 students at SMA Negeri 3 Bengkalis. This study consisted of 2 cycles, in each cycle consisting of 4 stages, namely Planning, Implementation, Observation and Reflection. This study involved 23 students of class X1 MIA 1 SMA Negeri 3 Bengkalis consisting of 10 male students and 13 female students. Before the implementing of the experimental method, the percentage of learning completeness was 17.39%, then after the first cycle of learning using the experimental method there was an increase in the percentage of learning completeness to 43.48%. In the second cycle succeeded in achieving the percentage of learning completeness 73.91%. The results showed that there was an increase in student achievement along with the implementation of the experimental method. Thus, the application of the experimental method can improve the physics learning achievement of class XI MIA 1 SMA Negeri 3 Bengkalis. ABSTRAKPenelitian tindakan kelas menggunakan metode eksperimen sebagai upaya peningkatan prestasi belajar fisika siswa. Pembelajaran metode eksperimen adalah cara belajar mengajar yang melibatkan siswa mengalami dan membuktikan sendiri proses dari hasil percobaan itu. Dengan eksperimen diharapkan siswa benar-benar dapat memahami konsep fisika yang dipelajari. Masalah yang mau dipecahkan adalah rendahnya prestasi belajar fisika yang ditunjukkan oleh hasil belajar fisika siswa kelas XI MIA 1 di SMA Negeri 3 Bengkalis. Penelitian ini terdiri dari 2 siklus, pada setiap siklus terdiri dari 4 tahapan, yaitu Perencanaan, Pelaksanaan, Observasi dan Refleksi. Penelitian ini melibatkan 23 orang siswa kelas X1 MIA 1 SMA Negeri 3 Bengkalis yang terdiri dari 10 siswa laki-laki dan 13 siswa perempuan. Sebelum diterapkannya metode eksperimen, persentase ketuntasan belajar yaitu sebesar 17,39 %, kemudian setelah dilaksanakan pembelajaran siklus 1 dengan menggunakan motode eksperimen ada peningkatan persentase ketuntasan belajar menjadi 43,48 %. Pada siklus 2 berhasil mencapai persentase ketuntasan belajar 73,91 %. Hasil penelitian menunjukkan bahwa terjadi peningkatan prestasi belajar siswa seiring dengan diterapkannya metode eksperimen. Dengan demikian, penerapan metode eksperimen dapat meningkatkan prestasi belajar fisika siswa kelas XI MIA 1 SMA Negeri 3 Bengkalis.